A 22,000-year tephrostratigraphy record of unidentified volcanic eruptions from Ternate and Tidore islands (North Maluku, Indonesia) - Faral, Audrey (Elsevier, 2022)
Investigating past eruptions gives a unique opportunity to understand volcanic hazards, particularly in Indonesia, where volcanic eruptions occur frequently. Here, we present the first reconstruction of the eruptive history of the Ternate and Tidore Islands (North Maluku, Indonesia) over the past 22,000 years cal. BP, based on a new identification and characterization of past volcanic events methodological approach. This multidisciplinary study (geomorphology, tephrochronology, sedimentology, geochronology, geochemistry) constitutes the first stratigraphic and chronological continuum from volcanic deposits found in a set of fifteen sections established in Ternate, Tidore, and Maitara Islands. Sedimentological and geochemical data from tephrostratigraphy studies and radio-carbon dating suggest that these islands experienced at least four major explosive events from c. 22,000 to 740 years cal. BP. The oldest event recorded is a Plinian eruption associated with a caldera-forming eruption of Telaga volcano on Tidore Island at c. 22,000–17,500 cal. BP. A second pumiceous eruption dated at c. 18,000 cal. BP is attributed to the last Plinian eruption of Gamalama volcano on Ternate, whose current eruptive activity is mainly strombolian or phreatomagmatic. A succession of pyroclastic deposits of phreatomagmatic origin is related to the Ngade maar formation on Ternate Island, and the abundant deposits of scoria, pumice, and ash found in all sites probably occurred c. 14,500–13,000 cal. BP. No eruptions of the Kie Matubu volcano on Tidore Island have been reported by human beings since their presence in the region from the 16th century, but this study highlights two late Holocene eruptions, c. 2500 cal. BP and 740 cal. BP. This first chronostratigraphic framework from the late Pleistocene to recent eruptions in this region, sheds new light concerning the management of prediction and warning information about potential eruptions that may occur on these small volcanic islands in the future.